Climate Change Impacts on the Future of Forests in Great Britain - Yu, Jianjun; Berry, Pam; Guillod, Benoit P.; Hickler, Thomas (Frontiers in Environmental Science, 2021)
Forests provide important ecosystem services, but are being affected by climate change, not only changes in temperature and precipitation, but potentially also directly through the plant-physiological effects of increases in atmospheric CO2. We applied a tree-species based dynamic model (LPJ-GUESS) at high 5 km spatial resolution to project climate and CO2 impacts on tree species and thus forest ecosystems in Great Britain. Climatic inputs consisted of a novel large climate scenario ensemble derived from a regional climate model under a RCP 8.5 emission scenario. The climate change impacts were assessed using leaf area index (LAI) and net primary productivity (NPP) for the 2030s and the 2080s compared to baseline (1975-2004). The potential CO2 effects, which are highly uncertain, were examined using a constant CO2 level scenario for comparison. Also, a climate vulnerability index was developed to assess the potential drought impact on modelled tree species. In spite of substantial future reductions in rainfall, the mean projected LAI and NPP generally showed an increase over Britain, with a larger increment in Scotland, northwest England and west Wales. The CO2 increase led to higher projected LAI and NPP, especially in northern Britain, but with little effect on overall geographical patterns. However, without accounting for plant-physiological effects of elevated CO2, NPP in Southern and Central Britain and easternmost parts of Wales showed a decrease relative to 2011, implying less ecosystem service provisioning, e.g. in terms of timber yields and carbon storage. The projected change of LAI and NPP varied from 5% - 100% of the mean change, due to the uncertainty arising from natural weather-induced variability, with Southeast England being most sensitive to this. It was also the most susceptible to climate change and drought, with reduced suitability for broad-leaved trees such as beech, small-leaved lime and hornbeam. These could lead to important changes in woodland composition across Great Britain.